Health‐related quality of life in patients with nonsurgical hypoparathyroidism and pseudohypoparathyroidism. (3rd April 2018) - Underbjerg, L.; Sikjaer, T.; Rejnmark, L.
Summary: Objective: Nonsurgical hypoparathyroidism (NS‐HypoPT) and pseudohypoparathyroidism (PHP) are rare diseases, with a prevalence of 2/100.000 and 1/100.000, respectively. Only few studies on Quality of Life (QoL) among patients with Ns‐HypoPT and PHP are available. We aimed to investigate the QoL among patients with Ns‐HypoPT and PHP including information about education. Design: A cohort study with patients identified from a previously epidemiological study. Patients: Fifty seven patients with Ns‐HypoPT and 30 patients with PHP. Measurements: The well‐validated questionnaires SF‐36v2 and WHO‐5 Well Being Index. Results compared to norm‐based material, disease‐specific norm‐based material and patients with postsurgical HypoPT Results: SF36v2 showed a significantly reduced score in all eight subdomains in patients with NS‐HypoPT compared with a norm‐based population. PHP patients scored lower in five subdomains. Females were more affected than males. Compared with postsurgical HypoPT, Ns‐HypoPT and PHP are compatible at most domains. At the domains Physical Function, Social Function and Mental Health, Ns‐HypoPT and PHP patients scored significantly lower ( P all  < .05). At the Mental Component Score, patients with Ns‐HypoPT had a lower score compared with postsurgical HypoPT ( P  < .01). The overall WHO‐5 Well Being Index score was comparable between groups ( P  = .45). No differences were seen comparing patients with postsurgical HypoPT and Ns‐HypoPT ( P  = .68) or postsurgical HypoPT and PHP ( P  = .67). A WHO‐5 score below 28 indicates depression (NS‐HypoPT=7; PHP=3, P  = .71), whereas a score between 28‐50 suggesting poor emotional well‐being (NS‐HypoPT=19; PHP=5, P  = .13). The remaining patients scored above 50 suggesting well‐being. Conclusion: QoL is impaired equally among patients with Ns‐HypoPT and PHP.